2012
DOI: 10.2174/187152012800228805
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic Targeting of Cell Death Pathways

Abstract: Cell death plays an important role in cancer growth and progression, as well as in the efficiency of chemotherapy. Although apoptosis is commonly regarded as the principal mechanism of programmed cell death, it has been increasingly reported that several anticancer agents do not only induce apoptosis but other forms of cell death such as necrosis, autophagy and mitotic catastrophe, as well as the state of permanent loss of proliferative capacity known as senescence. A deeper understanding of what we know about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…It has been reported that acute and chronic exposure to CP results in elevated apoptotic germ cell rates [5,24,25]. A caspase-dependent pathway could be triggered by chemotherapeutics [26].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that acute and chronic exposure to CP results in elevated apoptotic germ cell rates [5,24,25]. A caspase-dependent pathway could be triggered by chemotherapeutics [26].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of chemotherapeutic agents is largely dependent on their ability to inhibit the growth of tumor cells (1). A number of studies have demonstrated that certain phytochemicals present in medicinal herbs exert antitumor activity by inhibiting cancer cell growth (2).…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade, accumulating evidence has suggested that many cancer therapeutic agents induce apoptosis. Although the anticancer agent mechanisms of the apoptotic pathway are controversial, the killing of cancer cells through the induction of apoptosis has been recognized as a novel strategy for identifying chemotherapeutic as well as chemopreventive agents (10)(11)(12).…”
Section: Induction Of Apoptosis In Mda-mb-231 Human Breast Carcinoma mentioning
confidence: 99%